Determination of The Authority To Adjudicate Child Adoption For Muslims in Indonesia - Bintoro, Rahadi Wasi; Maryono, Antonius Sidik; Sanyoto, Sanyoto; Kupita, Weda; Prasetyo, Muhammad Bagus Tri (Faculty of Law, Universitas Jenderal Soedirman, 2021)
This article seeks to raise legal issues regarding child adoption, because adoption of children in the customary law system and Islamic law in Indonesia brings different legal consequences in family law. The focus of this study is to discuss the implications of the adoption of children in district courts and religious courts and the determination of the competence of the court in the adoption of children. This study uses normative research with a conceptual approach and legislation with the main data in the form of laws and regulations and the law of adoption. Based on the analysis, The Religious Judiciary uses the concept and legal basis of Islamic Law, while the General Judiciary uses the concept and legal basis in the form of Customary Law. Customary Law, adopted children have the same position, including in bequeathing, with the biological child, while in Islamic law does not know the concept of adopted children, but nevertheless for the benefit of the Compilation of Islamic Law gives the opportunity to the community to perform the adoption of the child.Keywords: adoption, customary law, Islamic law